DIMENSIONS OF AGGRESSION, TERRORISM INCLINATION AND AREA BOYS OF LAGOS METROPOLIS - Malomo, Bolajoko Ibiyemi; Ayemo, Olusegun Aboyowa (African Journal of Social and Behavioural Sciences, 2025)
The inclination tow terrorism may find its root in the personality variable of aggression. Area boys mean many things to many people, but usually, they invoke negative emotions. Observation of the activities of area boys indicates a manifestation of physical and verbal aggression against the general public. This present study therefore examined the independent relationships between four dimensions of aggression and terrorism inclination among area boys of Lagos metropolis. The terrorism inclination scale and a four-dimension aggression scale were presented to 214 area boys to measure the variables of interest in the study. The location of the study consists of Yaba, Ojota, Agege and Ogba bus stops. The result revealed that all the four dimensions of terrorism namely anger, hostility, physical aggression, and verbal aggression correlated positively with inclination towards terrorism. The physical and verbal dimensions of aggression correlated more than the dimensions of anger and hostility. It is recommended that the government intensify efforts to create energy-diffusing and constructive engagements for the area boys.